Heterogeneity of Tumors in Breast Cancer: Implications and Prospects for Prognosis and Therapeutics - Nigatu Tuasha; Beyene Petros (Scientifica)
Breast cancer is the most commonly diagnosed form of cancer in women comprising 16% of all female cancers. The disease shows high intertumoral and intratumoral heterogeneity posing diagnostic and therapeutic challenges with unpredictable clinical outcome and response to existing therapy. Mounting evidence is ascertaining that breast cancer stem cells (CSCs) are responsible for tumor initiation, progression, recurrence, evolution, metastasis, and drug resistance. Therapeutics selectively targeting the CSCs based on distinct surface molecular markers and enhanced intracellular activities of these cells continue to evolve and hold significant promise. Having plethora of heterogeneity accompanied with failure of existing conventional therapeutics and poor prognosis, the present review focuses on elucidating the main signaling pathways in breast CSCs as major therapeutic targets. The role of developments in nanomedicine and miRNA as targeted delivery of therapeutic anticancer agents is also highlighted.